The Impact of Divided Government and the Probabilities of Alternation in the Debt of Argentine Provinces (1996-2020) (Desarrollo Económico. Revista de Ciencias Sociales, 2023)
This article explains the levels of non-floating per capita debt of the twenty-four Argentine provinces in the period 1996-2020. Its main finding lie in the fact that divided government situations only restrict the possibilities of indebtedness when the opposition perceives the probability of an alternation in the provincial executive. In accordance with previous work carried out at the subnational level finances, the debt increases as the vertical fiscal imbalance enlarge, while it decreases when the percentage of provincial income in terms of royalties increases, and the primary budget result improves.
Keywords: Debt, Provinces, Opposition, Legislature, Royalties, Transfers